THE ORETICAL BASIS OF USING LABOR RESOURCES - Tillanazarov Zuhriddin To’xtamurod ugli (Лучшие интеллектуальные исследования, 2023)
Abstract: This article provides information on the theoretical basis of the use of labor resources and the disadvantages and advantages of the use of labor resources, the ways of rational use of labor resources, and the problems that may arise in their use.